Digital Ethics in Leadership Based on Ki Hadjar Dewantara Philosophy - Sri Watini; Budi Supriyatno (ADI Publisher, 2026)
Speaking ethics is one of the fundamental aspects in shaping a person's character and personality, especially leader of the nation who play an active role as role models in a pluralistic society. In the context of exemplary leadership, particularly in speaking, it provides a strong moral and spiritual foundation for building ethical, courteous, and leadership-oriented communication. This research aims to examine the concept of speaking ethics in providing exemplary leadership based on Ki Hadjar Dewantara's philosophy, emphasizing the application of the values